2001
DOI: 10.1271/bbb.65.1007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Binding Between the Rat Small Intestinal Brush-border Membrane and Dietary Proteins in the Sensory Mechanism of Luminal Dietary Proteins

Abstract: Dietary proteins are recognized by the gastrointestinal tract to display physiological functions, however, the sensory mechanism of the intestinal mucosa is not known. We examined binding properties between the rat small intestinal brush-border membrane (BBM) and proteins by using a surface plasmon resonance biosensor. BBM and solubilized BBM prepared from the rat jejunum bound to casein immobilized on the sensor surface, but not to bovine serum albumin. The ileal BBM showed less binding to casein than the jej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…These results suggest that casein and ␣-casein bind to STC-1 cell membrane components and that ␣-casein binds more readily than casein sodium. The difference between BSA and casein is consistent with previous observations with rat small intestinal brushborder membranes (20).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These results suggest that casein and ␣-casein bind to STC-1 cell membrane components and that ␣-casein binds more readily than casein sodium. The difference between BSA and casein is consistent with previous observations with rat small intestinal brushborder membranes (20).…”
Section: Resultssupporting
confidence: 92%
“…The supernatant was divided into aliquots and stored at −80°C. When the biosensor analysis was conducted, the aliquots were diluted 1:10 with HBS-E buffer before binding analysis (final concentration of Triton X-100 was 0.01%) (20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14) It has been suggested that binding of dietary proteins or peptides to the rat small intestinal brush-border membrane (BBM) is an integral part of a common sensory mechanism to release CCK. 15) We found that appetite suppression by BconP corresponds to the binding ability of this peptone to the rat small intestinal BBM as well as stimulation of CCK release directly from rat isolated dispersed intestinal mucosal cells. 14) Cellular preparations from rat isolated dispersed intestinal mucosa might not consist solely of CCKproducing I-cells due to cell heterogeneity in the intestinal mucosa.…”
mentioning
confidence: 73%
“…19) Briefly, the soluble components of rat intestinal BBM were prepared by solubilization with Triton X-100; they were immobilized as ligand over a flow cell surface (a test flow cell) of the CM5 sensor chip by an amine-coupling procedure. 15) Ethanolamine was immobilized onto another flow cell as a reference. Test peptone was dissolved (100 mg/ml) in HBS-E buffer containing 10 mM HEPES, 150 mmol/l NaCl, and 3 mmol/l EDTA, pH 7.4, and injected over both the test and reference flow cells at a rate of 10 ml/min for 2 min as the analyte.…”
Section: Methodsmentioning
confidence: 99%